2006
DOI: 10.1262/jrd.18043
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Localization of Fas Ligand and Fas During Atresia in Porcine Ovarian Follicles

Abstract: Abstract.To reveal the mechanisms regulating the selective atresia of follicles in porcine ovaries, we examined the changes in the mRNA and protein levels of cell-death ligand, Fas/APO-1/CD95 ligand (FasL), and its receptor, Fas/APO-1/CD95 (Fas), and the localization of the proteins in granulosa cells during follicular atresia using the reverse transcription-polymerase chain reaction (RT-PCR), Western blotting, and immunohistochemical techniques, respectively. Trace levels of FasL mRNA and protein were detecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
43
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 32 publications
3
43
0
Order By: Relevance
“…Granulosa cell apoptosis is the first event in follicular atresia and is mediated by cell death ligand and receptor systems [7,[26][27][28]. However, there is insufficient information on the role of intracellular signaling molecules in granulosa cells, especially downstream of the activated caspase-8.…”
Section: Discussionmentioning
confidence: 99%
“…Granulosa cell apoptosis is the first event in follicular atresia and is mediated by cell death ligand and receptor systems [7,[26][27][28]. However, there is insufficient information on the role of intracellular signaling molecules in granulosa cells, especially downstream of the activated caspase-8.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies demonstrated that TNF superfamily and TNFR superfamily proteins are also expressed in porcine ovarian follicles and that they are involved in regulation of survival and apoptosis of granulosa cells [27,[29][30][31][32]. Not only death receptors, but also decoy receptors were expressed in porcine ovarian follicles.…”
Section: Discussionmentioning
confidence: 99%
“…As previously reported [27], ovaries obtained from gilts at a local slaughterhouse were used. For the isolation of total RNA, tertiary follicles (3-4 mm in diameter) were dissected out using scalpels and classified into the healthy, early atretic and progressed atretic stages based on their morphology under a dissection microscope.…”
Section: Tissue Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dev. 56: [230][231][232][233][234][235] 2010) poptosis is a crucial mechanism in ovarian function through its significant contribution to cell deletion during follicular atresia [1][2][3][4][5] and luteal regression [6]. It is generally accepted that apoptosis is the main type of cell death during structural luteolysis in many species [7].…”
mentioning
confidence: 99%